The role of employment protection legislation regimes in shaping the impact of job disruption on older workers' mental health in times of COVID-19 - Cinzia Di Novi; Paolo Paruolo; Stefano Verzillo (European Commission, 2022)
This study exploits individual data from the 8th wave of the Survey of Health, Ageing and Retirement in Europe (SHARE) and the SHARE Corona Survey to investigate the mental health consequences of COVID-19 job disruption across different European countries. It focuses on older workers (aged 50 and over) who were exposed to a higher risk of infection from COVID-19 and were also more vulnerable to the risk of long-term unemployment and permanent labour market exits during economic downturns. The relationship between job disruption in times of COVID-19 and older workers' mental health is investigated using differences in country-level employment legislation regimes in the EU. European countries are clustered into three macro-regions with high, intermediate and low employment regulatory protection regulations, using the Employment Protection Legislation (EPL) aggregate score proposed by the OECD. Results reveal a clear EPL gradient: job disruption has a positive and significant impact on older workers' psychological distress especially in those countries where EPL is more binding. The present findings suggest possible mitigating measures for older unemployed in the EU countries with higher Employment Protection legislation.
Keywords: I14; I18; J08; 330; European Countries; COVID-19 pandemic; job disruption; mental health; older workers; EPL